Net Neutrality and the Battle for the Open Internet - Kimball, Danny (University of Michigan Press, 2022)
“Net neutrality,” a dry but crucial standard of openness in network access, began as a technical principle informing obscure policy debates but became the flashpoint for an all-out political battle for the future of communications and culture. Net Neutrality and the Battle for the Open Internet is a critical cultural history of net neutrality that reveals how this intentionally “boring” world of internet infrastructure and regulation hides a fascinating and pivotal sphere of power, with lessons for communication and media scholars, activists, and anyone interested in technology and politics. While previous studies and academic discussions of net neutrality have been dominated by legal, economic, and technical perspectives, Net Neutrality and the Battle for the Open Internet offers a humanities-based critical theoretical approach, telling the story of how activists and millions of everyday people, online and in the streets, were able to challenge the power of the phone and cable corporations that historically dominated communications policy-making to advance equality and justice in media and technology.